2016
DOI: 10.1021/acsinfecdis.5b00150
|View full text |Cite
|
Sign up to set email alerts
|

Bioautography with TLC-MS/NMR for Rapid Discovery of Anti-tuberculosis Lead Compounds from Natural Sources

Abstract: While natural products constitute an established source of lead compounds, the classical iterative bioassay-guided isolation process is both time- and labor-intensive and prone to failing to identify active minor constituents. (HP)TLC-bioautography-MS/NMR, which combines cutting-edge microbiological, chromatographic, and spectrometric technologies, was developed to accelerate anti-tuberculosis (TB) drug discovery from natural sources by acquiring structural information at a very early stage of the isolation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Moreover, using chemical methods to pursue biological targets creates incoherency between the methodology and the desired outcome. To overcome this disadvantage, a TLC-based bioautography was introduced [26,27]. The use of TLC in both the GUESS method and bioautography to visualize bioactivity creates seamless transition from chemical based fractionation to biological targets.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, using chemical methods to pursue biological targets creates incoherency between the methodology and the desired outcome. To overcome this disadvantage, a TLC-based bioautography was introduced [26,27]. The use of TLC in both the GUESS method and bioautography to visualize bioactivity creates seamless transition from chemical based fractionation to biological targets.…”
Section: Resultsmentioning
confidence: 99%
“…A recent report of RC by Grzelak et al may serve as a final example: two isoflavones that were isolated from an actinomycete extract showed >90% purity and MICs of 0.75 and 0.11 μg/mL against M. tb . 25 However, synthesized material of these compounds failed to demonstrate any anti- M. tb activity. TLC-bioautography in combination with MS and NMR confirmed that the isoflavone samples contained a potent cyclic heptapeptide, xylamycin, which had coeluted with the isoflavones in the initial isolation (manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
“…In order to make the results easier to observe, it is sometimes necessary to add a certain amount of tetrazolium salt to the nutrient medium, such as MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide), TTC (2,3,5,-Triphenyltetrazolium chloride) or INT (iodonitrotetrazolium chloride). Dehydrogenases of living microorganisms convert these salts into colored formazans, because MTT, INT and other tetrazolium salts are light in color and easy to be converted into darker compounds by bacterial metabolites, thus forming the background color, and, as a result, for MTT, yellow zones of inhibition are observed on a purple background [ 57 ].…”
Section: Biological Applicationsmentioning
confidence: 99%